Liberté d'expression et diffamation de collectivités : quand le droit à l'égalité s'exprime - Buron, Denis (Les Cahiers de droit, 1988)
Class defamation, for reasons of race, ethnic origin, religion or sex, is in the middle of a confrontation between many rights and liberties : On the one hand, freedom of expression, often considered the most fundamental of them all ; On the other, equality rights, freedom of opinion and the right to security of the person. This conflict may be viewed as a test for freedom of expression, hoping that truth will finally prevail, as well as a challenge for other liberties to be recognized. A choice has to be made : Should we protect expression, or should we protect collectivities from some expression ? The Canadian Charter of Rights and Freedoms, it is submitted, has already indicated the right direction : Sections 27 and 28, multiculturalism and sex equality, do in fact exclude class defamation from the protected freedom of expression. That which is currently the law of class defamation, as a consequence, will remain. But this might be an unfortunate blessing, since class defamation is virtually non-existent in Canadian law.